Right to Education - From Policy to Practice: Social Exclusion and Gender in Delhi's Primary Education System - Sutherland, Laura A. (Université d'Ottawa / University of Ottawa, 2016)
This thesis explores patterns of access and experiences of meaningful access under India’s Right of Children to Free and Compulsory Education Act, 2009 (RTE Act) from a critical gender perspective (Fraser, 1997; Jackson, 1999). Within the RTE Act, special attention is given to Section 12(1)(c), the free private school seats provision. The argument is that in order to fully analyze education progress, research must advance beyond focusing on physical access to exploring indicators of meaningful access. This thesis discusses the construction of a quantitative variable, ‘silent exclusion’, as a composite drawn from wider qualitative research. The first available data from the Insights into Education household survey in Delhi are analyzed using statistical and econometric techniques. It was found that private unaided recognized schools remain inaccessible for the most marginalized households. Child’s sex was not found to have a significant effect on school management choice, and both boys and girls attended privately and publically managed elementary schools in the sample. Four access issues pertaining to the free seat provision were identified: public awareness; reaching intended beneficiaries; low success rates for applicants; and continuing financial challenges for households accessing a free seat. In terms of children’s schooling experiences, low levels of silent exclusion were reported overall. Explicit displays of discrimination and exclusion were not found in the sample; however, less visible displays of exclusion were noted, such as a lack of leadership opportunities for children from lower income households, scheduled castes/tribes, and children attending government-managed schools. A lack of political and social pressure to fully implement the RTE Act at the local level is evident, which raises the question of how much a law in itself can bring about social change in the education sector.
Keywords: Education; India; Meaningful Access; Social Exclusion; Silent Exclusion; Gender